Colour discrimination among patients with schizophrenia in Lebanon. (1st June 2020) - Dahdouh, Oussama; Haddad, Chadia; Hany, Zeina; Azar, Georges; Lahoud, Corinne; Hallit, Souheil; Hachem, Dory
Abstract: Background: Abnormalities and contrast sensitivity have already been studied in schizophrenia. However, the relationship between symptom severity in schizophrenia and colour vision sensitivity has not been studied systematically. Aim: Our objective was to evaluate colour discrimination in patients with schizophrenia compared to controls and examine if this colour discrimination is correlated with schizophrenia symptoms' severity. Methods: This case–control study, performed between January and April 2017, included 50 schizophrenic patients and 50 healthy controls matched for age and sex. The Positive and Negative Symptoms Scale (PANSS) was used to determine the schizophrenia symptoms' severity. Colour discrimination was evaluated using the total error score (TES) generated using the Farnsworth D-15 test. The higher the TES, the more severe colourblindness. Results: A significantly higher mean TES was found in schizophrenics (30.32) compared to healthy patients (13.07) ( p < 0.001). Colour blindness was correlated to the severity of schizophrenic symptoms only in the subgroup of patients with severe schizophrenia. Conclusion: Colour vision defect is a common feature in schizophrenia, and may be more significant when related to psychotic symptoms. KEY POINTS: A significantly higher mean TES was found in schizophrenics compared to healthy patients. Colour blindness was correlated to the severity of schizophrenic symptoms only in the subgroup of patients with severe schizophrenia. Colour vision defect is a common feature in schizophrenia, and may be more significant when related to psychotic symptoms.